Mechanism and kinetics of Cr(VI) adsorption on biochar derived from Citrobacter freundii under different pyrolysis temperatures. (June 2022) - Singh, Simranjeet; Anil, Amith G.; Naik, T.S. Sunil Kumar; U., Basavaraju; Khasnabis, Sutripto; Nath, Bidisha; Kumar, Vineet; Subramanian, S.; Singh, Joginder; Ramamurthy, Praveen C.
Abstract: The use of bacterial biochar for Cr(VI) removal opens room for new research in terms of cost-effectiveness, better performance and high selectivity. This work reports the synthesis, physicochemical characterization and performance evaluation of bacterial biochar synthesized at 200 °C and 400 °C. To examine the removal mechanism and behaviour, batch mode experiments were conducted by modifying different parameters such as dosage, pH, initial ion concentration and temperature. The capacity of the biochar for removing Cr(VI) was found to be qmax  = 19.43 mg/g (200 °C) and 29.73 mg/g (400 °C). The BET surface area of bacterial biochar (400 °C) is also seen to decrease from 22.09 m 2 /g to 3.17 m 2 /g. The decrease in pore volume and surface area makes successful adsorption evident. In addition to this, the adsorption data were adequately simulated with Langmuir, Freundlich and Temkin and pseudo-second kinetics suggesting that the adsorption process were the combination of external mass transfer and chemisorption. Electrostatic interactions were determined to be the dominant removal mechanism. Biochar pyrolyzed at 400 °C serves as good adsorbent material to remove Cr(VI) from aqueous solutions. It can also be a suitable material for removing emerging contaminants from aqueous solutions. Graphical abstract: Unlabelled Image Highlights: Cr(VI) adsorption study done onto bacterial carbon at two different pyrolysis temperatures. The adsorption process is spontaneous and endothermic. The maximum adsorption capacity is higher in the case of 400 °C pyrolyzed biochar. Electrostatic interactions were determined to be the dominant removal mechanism.